Wiggling the Frame: “Philadelphia Assembled” and “Trainings for the Not-Yet” - Jeanne van Heeswijk; Maria Hlavajova; Damon Reaves; Mick Wilson (Parse Journal, 2021)
In a conversation between the artist Jeanne van Heeswijk, the artist and educator Damon Reaves and the organizer, educator, and Artistic Director of BAK, basis voor actuele kunst, Utrecht Maria Hlavajova, moderated by Mick Wilson, the methodologies, dynamics, circumstances, effects and challenges of two exceptional and highly considered exhibitionary processes–“Philadelphia Assembled” (Philadelphia Museum of Art, 2014-17) and “Trainings for the Not-Yet” (BAK, 2019-20)–are explored with particular reference to forms of becoming collective, and diverse modes of agency within exhibition.